The ABC of the OPT : a legal lexicon of the Israeli control over the occupied Palestinian territory / Orna Ben-Naftali, Michael Sfard, Hedi Viterbo. - Ben-Naftali, Orna; Sfard, Michael, 1972-; Viterbo, Hedi (Cambridge University Press, 2018)
Israel's half-a-century long rule over the West Bank and Gaza Strip, and some of its surrounding legal issues, have been the subject of extensive academic literature. Yet, to date, there has been no comprehensive, theoretically-informed, and empirically-based academic study of the role of various legal mechanisms, norms, and concepts in shaping, legitimizing, and responding to the Israeli control regime. This book seeks to fill this gap, while shedding new light on the subject. Through the format of an A-Z legal lexicon, it critically reflects on, challenges, and redefines the language, knowledge, and practices surrounding the Israeli control regime. Taken together, the entries illuminate the relation between global and local forces - legal, political, and cultural - in Israel and Palestine. The study of the terms involved provides insights that are relevant to other situations elsewhere in the world, particularly with regard to belligerent occupation, the law's role in relation to state violence, and justice.